Gender differences in self-rated health among older adults in the Chinese workforce - Li, Wenyu; Xu, Zhijie; Tang, Wenjie (Frontiers in Public Health, 2024)
IntroductionThis study investigates gender-based disparities in self-rated health among older individuals in the Chinese workforce, utilizing data from the China Health and Retirement Longitudinal Study (CHARLS). Understanding these health gaps is crucial for crafting effective health policies and interventions in light of the rapidly aging population.Materials and methodsData from the 2020 CHARLS survey, comprising Chinese individuals aged 45 and above, were analyzed, focusing on older adults actively employed. Descriptive statistics and regression analyses examined gender discrepancies in self-rated health, considering diverse sociodemographic, economic, and health-related factors.ResultsGender disparities in demographics, work environments, and self-rated health were observable among male and female participants. Older males tended to have higher rates of smoking and alcohol consumption, coupled with lower incomes. In contrast, females exhibited healthier behaviors influenced by access to healthcare and lifestyle modifications. For males, economic stability and moderate alcohol use positively influenced self-rated health, while females benefited from healthcare coverage and healthy lifestyle choices. Tailored gender-specific health interventions should prioritize these unique factors to enhance overall well-being.DiscussionDiscussions highlighted the impact of demographic variables, including age, marital status, social security, and employment conditions, on self-rated health. The study emphasized the crucial role of marital relationships in the health outcomes of older adult workers.ConclusionThis study underscores the pivotal role of gender in self-rated health variations and provides essential insights for targeted interventions. By considering both quantitative and qualitative determinants of well-being, focused health policies can effectively address the health and well-being of aging populations, especially older adult workers.